Diets of mammalian fossil fauna from Kanapoi, northwestern Kenya. Issue 140 (March 2020) - Manthi, Fredrick K.; Cerling, Thure E.; Chritz, Kendra L.; Blumenthal, Scott A.
Abstract: Carbon isotope ratios of mammalian teeth from the Kanapoi site in northern Kenya are interpreted in the context of C3 and C4 derived resources to investigate the paleoecology of Australopithecus anamensis . δ 13 C values of large mammals, when compared at the taxon level, show an ecosystem that is strongly biased towards mixed feeders and browsers. However, sufficient C4 resources were present such that some C4 dominated grazers were also present in the large mammal fauna. Analyses of micromammals shows that their diets were C3 dominated or C3 –C4 mixed. Carbon isotope studies of primates shows that the major primate tribes—Colobini, Papioini, Hominini—all made some use of C4 resources in their respective diets; the Hominini had a higher fraction of C3 diet resources than the other primate tribes represented in the fossil record.